A-OLSR: ANFIS based OLSR to select Multi point relay - Vivek Sharma; Bashir Alam; M. N. Doja (Institute of Advanced Engineering and Science, 2019)
The characteristics like dynamic topology, power consumption, mobility etc. may leads to affect the routing process of packet as it progresses from one node to another node. The energy of each node is very limited in MANET’s due to which it becomes an important parameter to be considered while selecting the route. The ‘Optimized Link State Routing Protocol’ (OLSR) does not consider node energy during Multipoint relay (MPR) selection process. This paper proposes an improvement of OLSR routing protocol named as A-OLSR protocol using node energy during its MPR process. The improvement is based on adaptive neuro fuzzy inference system (ANFIS). The network simulator NS2.35 is used for the simulation, random way point model for mobility and constant bit rate (CBR) for traffic process. The performance of proposed A-OLSR protocol is evaluated using the packet delivery ratio (PDR) and end to end delay metrices. The simulation results prove the superiority of the proposed protocol in terms of PDR.